2013
DOI: 10.7860/jcdr/2013/5464.3335
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Diabetes Mellitus

Abstract: Introduction: Diabetes Mellitus is the commonest major metabolic disease and most prevalent diseases worldwide. Its related morbidity is due to its micro and macro angiopathic complications. Aim:The aim of this study was to measure and compare the serum levels of zinc and magnesium in normal individuals and in diabetic patients.Method: Analysis of minerals was done in plasma by using a Varian Spectra AA 220 model atomic absorption spectrophotometer. Result:Our observations showed a definite lowering of serum m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
(20 reference statements)
2
26
0
Order By: Relevance
“…A total of 97 articles were retrieved, with a final number of 52 case-control studies (1, 4, 19, 20, 22–25, 35–79) with 20183 participants were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 97 articles were retrieved, with a final number of 52 case-control studies (1, 4, 19, 20, 22–25, 35–79) with 20183 participants were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired secretion of this protein affects glucose metabolism, and consequently, results in hyperglycemia. (1) Unregulated levels of blood glucose can lead to several debilitating conditions such as nephropathy, neuropathy, retinopathy, cardiovascular disease, stroke, and amputations of extremities. (2) About 90 to 95% of the patients are affected by type 2 diabetes (2) which is characterized primarily by insulin resistance, hyperinsulinemia, and beta-cell dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies showed insignificant difference of serum zinc and magnesium among T2DM patients and nondiabetes study subjects,26–28 which are inconsistent with the current finding. Zinc and magnesium are essential trace metal elements crucial for the function of more than 300 enzymes 2933. The trivalent chromium is often required for the maintenance of normal glucose34 and fat metabolism 35.…”
Section: Discussionmentioning
confidence: 99%
“…However, zinc, magnesium, and chromium deficiency often leads to insulin resistance 2937. The exact physiologic mechanism of zinc, magnesium, and chromium deficiency among T2DM patients is unknown, but high urinary loss has been observed as a result of the osmotic effect of glycosuria 20,25,33. Increased serum iron and ferritin concentrations have been reported to be associated with insulin resistance 3845.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia and hypozincemia have been noted repeatedly (1315). Concentrations in blood plasma, which is the source for most clinical tests, do not necessarily reflect the status of biometals or biominerals in tissues.…”
Section: Biometals In Diabetesmentioning
confidence: 99%